Evaluation of Cardiospermum halicacabum leaf compounds against human DihydroOrotate Dehydrogenase: a target for Rheumatoid Arthritis using Structure based Drug Designing - Priya Swaminathan, Lilly Saleena (Journal of Applied Pharmaceutical Science, 2017)
Rheumatoid arthritis [RA] is a disorder that makes the abnormal immune cells to assail the joints in the body leading to pannus formation and destruction of the synovium. Human DiHydroOrotate DeHydrogenase [hDHODH] inhibition is effective in controlling the proliferation of the abnormal immune cells. Though technology has benefitted science and medicine in many ways, certain indigenous cures are still considered a boom for various diseases. C. halicacabum an Indian medicinal plant is widely used as a home remedy for arthritis pain. The novelty of this study relies on the extensive validations performed to obtain robustness of the results. An E-pharmacophore model based on A771726- an experimentally resolved inhibitor of hDHODH was screened against the phytocompounds in the leaf of C. halicacabum. These compounds were docked and further validated statistical and ranking methods. Further, flexible docking was performed to understand the optimal pose of the docked structures of Apigenin 7O-glucornide and Luteolin 7O-glucornide. These optimal poses were then simulated for 10 ns in a SPC environment which gave a very low RMSD value of 1.5 Å. These results were comparable with the known inhibitor of hDHODH. Thus this study helps to understand and evaluate the different probable inhibitors of hDHODH from C.halicacabum and suggests a mode of action for phytochemicals of C. halicacabum against RA.
Keywords: Rheumatoid arthritis, C. halicacabum, Dihydroorotate Dehydrogenase, Screening validation .